Cerebrocortical necrosis in small ruminants in Argentina: a case series = Necrosis cerebrocortical en pequeños rumiantes en Argentina: reporte de casos - Marron, Yolanda Mabel (2024)
Several neurological diseases can affect small ruminants. Cerebrocortical necrosis (CCN) is a pathology associated with different etiologies. One of them, nutritional polioencephalomalacia (PEM) is a common metabolic disease associated to intensive production systems. We report eight outbreaks of CCN in small ruminants (goats and sheep) of different regions of Argentina, probably associated to ruminal acidosis, elevated levels of sulfur in the forage and water and/or suspected lead poisoning. Affected sheep and goats developed sudden neurological signs such as ataxia, amaurosis, opisthotonus, dissociation, lethargy, hypextension of the limb, lateral decubitus, and death. Postmortem examination of six animals was performed, and gross lesions were scarce, characterized as cerebrocortical malacia. Histologically, severe cerebrocortical laminar necrosis was observed. Based in these findings and/or response to thiamine and dexamethasone treatment in four outbreaks, a diagnosis of CCN was achieved, of different suspected origins. This disease is commonly associated with intensive production systems, and therefore, coud be underdiagnosed in extensive conditions, more frequently used for small ruminant rearing.